2003
DOI: 10.1038/sj.mp.4001340
|View full text |Cite
|
Sign up to set email alerts
|

Screening of nine candidate genes for autism on chromosome 2q reveals rare nonsynonymous variants in the cAMP-GEFII gene

Abstract: The results from several genome scans indicate that chromosome 2q21-q33 is likely to contain an autism susceptibility locus. We studied the potential contribution of nine positional and functional candidate genes: TBR-1; GAD1; DLX1; DLX2; cAMP-GEFII; CHN1; ATF2; HOXD1 and NEUROD1. Screening these genes for DNA variants and association analysis using intragenic single nucleotide polymorphisms did not provide evidence for a major role in the aetiology of autism. Four rare nonsynonymous variants were identified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 38 publications
3
77
0
Order By: Relevance
“…On the long arm of chromosome 2, GAD1, NOSTRIN, KCNH7, TBR1, DLX1 and DLX2, were identified for their role in brain function, with several of these genes involved in glutamanergic neural transmission (which is theorised to influence prefrontal cortex functioning; Huntsman et al, 1998). Some of these genes (GAD1, DLX1 & 2, TBR1) have been tested for their association with autism, which is linked to this same region of chromosome 2 (Bacchelli et al, 2003;Rabionet et al, 2004). While association was not supported for autism, it is possible that these genes play a role in cognitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…On the long arm of chromosome 2, GAD1, NOSTRIN, KCNH7, TBR1, DLX1 and DLX2, were identified for their role in brain function, with several of these genes involved in glutamanergic neural transmission (which is theorised to influence prefrontal cortex functioning; Huntsman et al, 1998). Some of these genes (GAD1, DLX1 & 2, TBR1) have been tested for their association with autism, which is linked to this same region of chromosome 2 (Bacchelli et al, 2003;Rabionet et al, 2004). While association was not supported for autism, it is possible that these genes play a role in cognitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…No clear evidence for association of any of the new variants with AD was found despite relatively high LOD scores from linkage analyses in the assessed samples. 38,[155][156][157] Four independent studies compared two single-nucleotide polymorphisms (SNPs) in the gene for the mitochondrial aspartate/glutamate carrier SLC25A12 in family-based and case-control association studies. Two studies 158,159 found an increased risk for autism associated with the haplotype GG (reverse strand) = CC (sense strand) consisting of SNPs rs2056202 and rs2292813.…”
Section: Chromosomementioning
confidence: 99%
“…Previously, we have identified in a patient with SCZ a de novo exonic microdeletion affecting another member of the RAPGEF family (RAPGEF6) located within a SCZ susceptibility locus at chromosome 5q (15). Mutations in another member of this family (RAPGEF4) have been described in autism (27).…”
Section: Patient Cohortsmentioning
confidence: 99%